High-Power Single-Mode 1.3-m InGaAsP-InGaAsP Multiple-Quantum-Well Laser Diodes With Wide Apertures - Kim, Kyoung Chan; Jang, Dong-Kie; Lee, Jung Il; Kim, Tae Geun; Lee, Woo Won; Kim, Jeong Ho; Yang, Eun Jeong; Koo, Bon Jo; Han, Il Ki (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2009)
A wide-aperture ridge waveguide structure was applied to 1.3-m InGaAsP-InGaAsP multiple-quantum-well laser diodes (LDs) to increase their maximum kink-free output power under single-lateral-mode operations. As a result, a kink-free output power up to 140 mW and an external efficiency of 0.3 W/A were achieved from a single facet of the LD with a 7-mu m-wide ridge top and a 1.5-mm-long uncoated cavity.